Thermal Properties And Ground-State Structures Of Pure And Alloy Nanoclusters Via Molecular Dynamics Simulation - Ong, Yee Pin (2018)
The study of thermal properties of nanoclusters via molecular dynamics simulation is a common research topic in computational physics. However, the methods of post-processing and determining the pre-melting and melting range of nanoclusters at specific composition differ in every research. In this thesis, the study of thermal properties was started by obtaining the ground-state structure of 38-atoms gold-platinum nanoclusters of various composition (where ) using Parallel Tempering Multicanonical Basin Hopping plus Genetic Algorithm (PTMBHGA). Bimetallic nanocluster with D6h symmetry has been selected for further investigation in the thermal properties, as it is the most stable bimetallic nanocluster studied in this thesis.